The New FibroScan-AST (FAST) Score: Enhancing Diabetes Mellitus Impact on Metabolic-Associated Fatty Liver Disease - Vítor Macedo Silva; Marta Freitas; Sofia Xavier; Pedro Boal Carvalho; Joana Magalhães; Carla Marinho; José Cotter (GE: Portuguese Journal of Gastroenterology, 2022)
Background: Metabolic-associated fatty liver disease (MAFLD) is an increasingly prevalent cause of chronic liver disease. In 2020, the FibroScan-AST (FAST) score was internationally validated as a new tool able to identify patients with steatohepatitis who benefit the most from further therapies, based on liver transient elastography (LTE) findings and serum levels of aspartate aminotransferase (AST). We aimed to identify, in MAFLD patients, which metabolic features may predict a higher FAST score. Methods: Retrospective study of consecutive patients with MAFLD submitted to LTE for two consecutive years. Patients without an AST sample collected within 6 months of the LTE were excluded. FAST score was calculated, stratifying the patient’s risk as low (<0.35), medium (0.35–0.67), or high (>0.67). Results: The sample included 117 patients, 53.0% of the female gender, with a mean age of 53 years. On multivariate analysis, patients with type 2 diabetes (T2DM) (p < 0.001), dyslipidemia (p = 0.046), and smoking habits (p = 0.037) presented with significantly higher FAST score values. Furthermore, diabetic patients did not only present significantly higher FAST scores but were also more frequently assigned to the high-risk group according to FAST score criteria (OR = 9.2; 95% CI = 1.8–45.5; p = 0.007). Conclusions: Calculating the FAST score, patients with T2DM presented a significantly higher risk of having significant fibrosis and steatohepatitis. Physicians may rely on this validated instrument to more easily identify which patients with T2DM and MAFLD benefit the most from a specialized follow-up.